Digital signal processor in optical tomography system - Mohd. Muji, Siti Zarina (Penerbit UTM, 2010)
Optical tomography involves the use of non-invasive optical sensors to obtain vital information in order to produce images of the dynamic internal characteristics of process system (Ibrahim et al., 2000). The use of optical sensors has the advantages of being conceptually straightforward and relatively inexpensive (Pang et al., 2004). Its working principle involves projecting a beam of light through a medium from one boundary point and detecting the level of light received at another boundary point (Rahim, 1996). A typical optical tomography system usually used DAQ to perform data acquisition tasks and host computer to carry out image reconstruction. However, only some of the functions provided by the DAQ were implemented.